Curriculum Design Based on Pesantren Values and Learning Models at MI Tarbiyatul Islamiyah Pati and SD Daarul Quran Semarang - Sholihah, Hidayatus; Zaenurrosyid, Ahmad (Jurnal As Sibyan, 2025)
Curriculum and learning management are two strategic components in determining the quality of primary education. Each educational institution develops its curriculum model according to its institutional vision, socio-cultural context, and long-term learning objectives. The differing characteristics between traditional Islamic schools and internationally based primary schools reflect a diversity of approaches in designing and managing learning processes. In this context, this study examines the curriculum design models and learning management implemented at MI Tarbiyatul Islamiyah Pati and DaQu Primary School, Semarang. Using a qualitative approach with a comparative case study method, data were collected through observation, in-depth interviews, and document analysis. The findings show that MI Tarbiyatul Islamiyah Pati integrates the National Curriculum with a local curriculum based on Islamic values, employing a character-based learning approach and habitual worship practices. Meanwhile, DaQu Primary School Semarang adopts the National Curriculum and the Cambridge International Curriculum with an orientation toward 21st-century skills and technology-based learning. Significant differences are observed in curriculum orientation, teacher roles, evaluation methods, and classroom management systems. However, each institution possesses contextual strengths that can serve as inspiration for developing a hybrid curriculum model. This study recommends a collaboration of religious values and global approaches in designing adaptive and holistic primary education.